Applying MDE tools to defining domain specific languages for model management - Pérez, Gabriela Alejandra (2013)
In the model driven engineering (MDE), modeling languages play a central role. They range from the most generic languages such as UML, to more individual ones, called domain-specific modeling languages (DSML). These languages are used to create and manage models and must accompany them throughout their life cycle and evolution. In this paper we propose a domain-specific language for model management, to facilitate the user's task, developed with techniques and tools used in the MDE paradigm.